The evolution of uncertainty in second opinions about prostate cancer treatment. (18th May 2017) - Hillen, Marij A.; Gutheil, Caitlin M.; Smets, Ellen M. A.; Hansen, Moritz; Kungel, Terrence M.; Strout, Tania D.; Han, Paul K. J.
Abstract: Background: People who have cancer increasingly seek second opinions. Yet, we know little about what motivates patients to seek them and how beneficial they are. Uncertainty—experienced by patients or communicated by physician and patient—may be crucial throughout the second opinion process. Objective: This study sought to investigate (1) how uncertainty influences men with prostate cancer to seek second opinions and (2) how second opinions may affect these patients' sense of uncertainty and subsequent experiences with their care. Methods: A qualitative study using semi‐structured interviews was performed. Men with localized or advanced prostate cancer (n=23) were interviewed by telephone about their motivations and experiences with seeking second opinions and the uncertainties they experienced. Analysis was performed using the constant comparative method. Results: Patients sought second opinions because they were uncertain about receiving too little or biased information, experienced insufficient support in coming to a treatment decision, or because physicians expressed different levels of uncertainty than they did ("unshared uncertainty"). Uncertainty was reduced by the second opinion process for most patients, whereas for others, it increased or was sustained. This evolution depended on the way uncertainty was addressed during the second opinion consultation. Conclusions: Second opinions may be a useful tool for some but not all patients. They should be used judiciously and not be viewed as a solution for current limitations to health‐care organization. An important yet challenging task for physicians is to focus less on information per se and more on how to assist patients manage irreducible uncertainty.